3-D fabrication using electrical discharge-milling: an overview. Issue 11 (18th August 2022) - Singh, Mahavir; Jain, V. K.; Ramkumar, J.
ABSTRACT: The electrical discharge machining (EDM) process has predominantly gained considerable impetus in the varieties of high-tech areas for impeccable machining of complex microfeatures in ultra-hard and exotic materials. The development of computer numerical control (CNC) of machine tools has permitted to explore the capabilities of the EDM process for the fabrication of three-dimensional (3-D) micro/macro features employing the controlled movement of the simpler tools in all three axes ( x -, y - and z -axes) in addition to the high-speed rotation about its axis. This variant of the EDM process, which entails a simple cylindrical/rectangular/square cross-section tool to accomplish the intended shape by following the programmed instructions is termed as electrical discharge-milling (ED-Milling) operation. In this review article, an endeavor has been made to present the state-of-the-art research that has been accomplished in ED-Milling and the allied EDM processes for 3-D machining. The article reviews the comparative study of majorly available micro-fabrication techniques, different means of complex 3-D fabrication using spark erosion phenomena, machining performance enhancement methods, material aspects, tool wear analysis and sustainable dielectrics in the ED-Milling. Critical assessment and prospects in the respective areas of research in ED-Milling are recommended.